Methane emissions from tree stems – current knowledge and challenges: an introduction to a Virtual Issue - Barba,J; Brewer,PE; Pangala,SR; Machacova,K (New Phytologist, 2024)
This article is a Commentary on the Virtual Issue ‘Methane emissions from tree stems – current knowledge and challenges’ that includes the following papers: Barba et al . (2019), Bréchet et al . (2021), Covey & Megonigal (2019), Feng et al . (2022), Flanagan et al . (2021), Jeffrey et al . (2019, 2021, 2023), Kohl et al . (2019), Machacova et al . (2021a,b, 2023), Megonigal et al . (2020), Pangala et al . (2013, 2014), Pitz & Megonigal (2017), Plain et al . (2019), Putkinen et al . (2021), Sjögersten et al . (2020), Takahashi et al . (2022), Tenhovirta et al . (2022), Wang et al . (2016), and Yip et al . (2018). Access the Virtual Issue at www.newphytologist.com/virtualissues .